Infographic. Useful steps in the prevention of illnesses during international athletics championships - Edouard, P.; Glover, D.; Murray, A.; Timpka, T.; Sorg, M.; Depiesse, F.; Branco, P.; Junge, A. (British Journal of Sports Medicine, 2020)
Illnesses can impair sports participation and performance in athletics training or competition (including major championships).1 Travel, jet lag, changes in climatic/environmental conditions and changes in food habits, in addition to the competition per se, could predispose athletes to illness in major championships context.